PEMBUATAN PEREKAT FENOLIK DARI LINDI HITAM YANG DIPEKATKAN DENGAN TANIN ATAU FENOL KRISTAL - R Sudradjat; G Pari; M I lskandar (Jurnal Penelitian Hasil Hutan, 2003)
Phenol  compounds  in  waste  water  of  pulp  and  paper  industry  are  toxic  and  harmful  to  environment.  Phenol  compounds  are  also  an  expensive  chemical  with  wide  range  uses,  such  as  raw  materials  for  the  manufacture  of  phenol  formaldehyde  glue.This  experiment  was  aimed  at  looking  into  appropriate  method  to  cope  with  the  problems  of  black  liquor's  phenol  by  converting  it  to  the  most  valuable  glue  largely  and  widely  used  in  the  plywood  industries,  i.e.  phenol-formaldehyde.  The  experiment  was  divided  into  three  stages,  i.e. (a)  recovery  of  phenol  from  black  liquor  after  distillation;  (b)  selecting  phenol  compounds  from  another  source  as  an  additive  to  increase  the  existing  phenol  concentration    in  the  distilled  black  liquor;  and  (c)  working  out  optimum  phenol  concentration  able  to  develop  maximum  bonding  strength  of  the  phenol-formaldehyde  glue.Phenol compounds investigated as an additive to increase  distilled phenol  concentration are  crystal  phenol  and  tannin.  The  two  additives  were  added  in  ratio  of  1:3,  1:5  and  1:7  (crystal  phenol/tannin  to  distilled  phenol).  After  that,  the  mixture  is  reacted  with  formalin  to  form  phenol  formaldehyde  glue  following  standard  procedure.  The  phenol  formaldehyde  glue  was  applied  to  plywood  and  then  was  analyzed  for  moisture  content,  density  and  bonding  strength.Results  showed  that  phenol  crystal  addition  is  better  than  tannin  due  to  lower  in  moisture,  but  higher  in  density  and  bonding  strength. At  all  mixture  ratio,  tannin  addition  gave  lower  plywood  bonding  strength  compare  to  standard  (14  kg/cm2),  but  phenol  addition  gave  higher  plywood  bonding  strength  (18-24 kg/cm2).  Further  experiment  should  be  conducted  to  use  crystal  phenol  as  an  additive  to  increase  distilled  phenol  concentration.